2011
DOI: 10.1007/s00417-011-1886-3
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity profiles of subretinal indocyanine green, Brilliant Blue G, and triamcinolone acetonide: a comparative study

Abstract: Subretinal ICG induces histological and functional damage to the retina, suggesting that ICG should be used with caution in macular hole surgery, where subretinal migration can occur. In contrast, BBG and TA appear safe after subretinal injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 55 publications
1
24
0
1
Order By: Relevance
“…In pig eyes, histopathologic and electrophysiologic evaluations 6 weeks after subretinal injection of ICG, BBG, or TA indicated that ICG evidently injures the retina both histologically and functionally, while BBG and TA do not [20], which is consistent with the results of this study. In that previous study, for patients with an MH or a macular pucker, ILM sections peeled off after staining with trypan blue, BBG, bromophenol blue, Chicago blue, or ICG were morphologically compared under a transmission electron microscope.…”
Section: Discussionsupporting
confidence: 91%
“…In pig eyes, histopathologic and electrophysiologic evaluations 6 weeks after subretinal injection of ICG, BBG, or TA indicated that ICG evidently injures the retina both histologically and functionally, while BBG and TA do not [20], which is consistent with the results of this study. In that previous study, for patients with an MH or a macular pucker, ILM sections peeled off after staining with trypan blue, BBG, bromophenol blue, Chicago blue, or ICG were morphologically compared under a transmission electron microscope.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, many studies supported the safety of this dye. 49,50 Because the GC-IPL defects were well circumscribed and not diffuse, the hypothesis for the toxic effect of the dye on the GC-IPL could be eliminated, leaving only the mechanical manipulation as a possible explanation.…”
Section: Discussionmentioning
confidence: 99%
“…Subretinal ICG induces histological and functional damage to the retina, suggesting that ICG should be used with caution in macular hole surgery, where subretinal migration can occur. In contrast, BBG and triamcinolone acetonide appear safe after subretinal injection [22]. …”
Section: Discussionmentioning
confidence: 99%